Porous Ni–Cr–Fe alloys as cathode materials for the hydrogen evolution reaction. Issue 56 (25th May 2016) - Xiao, Yifeng; Liu, Yan; Tang, Zhi; Wu, Liang; Zeng, Yi; Xu, Yanfei; He, Yuehui
Abstract : We report porous Ni–Cr–Fe cathode materials which possess high stability during prolonged electrolysis and good corrosion resistance in 6 M KOH, exhibiting promising characteristics as cathodes for the HER on an industrial scale. Abstract : The objective of this work was to investigate the electrocatalytic efficiency and stability of porous Ni–Cr–Fe cathode materials, obtained by reactive synthesis of Ni, Cr and Fe elemental powders, using cyclic voltammetry, cathodic polarization and impedance spectroscopy techniques. The kinetic parameters have been determined from an electrochemical steady-state polarization technique in 6 M KOH solution. The Tafel slope of the best-performing porous Ni–Cr–Fe cathode materials is −130 mV dec −1, and the exchange current density is 7 × 10 −4 A cm −2 at elevated temperature. Moreover, the porous Ni–Cr–Fe cathode materials possess high stability during a prolonged electrolysis process. The results suggest that the significant catalytic and stability performances of the materials are from the high real surface area and good intrinsic catalytic effect.